2005
DOI: 10.1046/j.1469-1809.2005.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dystrophin Gene Deletions Indicates that the Hinge III Region of the Protein Correlates with Disease Severity

Abstract: SummaryWe have investigated the frequency of deletions in the dystrophin gene in 108 unrelated Duchenne and Becker muscular dystrophy (DMD/BMD) patients from southern Italy (DMD, n. 47; BMD, n. 61) and identified 89 deletions. The de novo mutation rate (about 30%), and the preferentially maternal origin of deletional mutations, analysed in families in which the maternal grandparents were available or their haplotypes could be unequivocally reconstructed, are in agreement with data reported for other population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 14 publications
4
22
0
Order By: Relevance
“…The last two associates tightly with the large oligoprotein complex of sarcolemmal glycoproteins. 20 In the deletions at the 5' end of the gene the author did not observe any discrepancy to the reading frame rule, as reported by others and attributed to transcription from alternate promoters and aberrant splicing. 20 In the central hot spot region some deletions starting with exon 45 and exon 46, though in frame, were found in DMD patients.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The last two associates tightly with the large oligoprotein complex of sarcolemmal glycoproteins. 20 In the deletions at the 5' end of the gene the author did not observe any discrepancy to the reading frame rule, as reported by others and attributed to transcription from alternate promoters and aberrant splicing. 20 In the central hot spot region some deletions starting with exon 45 and exon 46, though in frame, were found in DMD patients.…”
Section: Discussionsupporting
confidence: 65%
“…20 In the deletions at the 5' end of the gene the author did not observe any discrepancy to the reading frame rule, as reported by others and attributed to transcription from alternate promoters and aberrant splicing. 20 In the central hot spot region some deletions starting with exon 45 and exon 46, though in frame, were found in DMD patients. This region constitutes the so-called Hinge III region and certain amino acids here must have other specific amino acids in their neighborhoods for desirable protein conformation.…”
Section: Discussionsupporting
confidence: 65%
“…In fact, in-frame deletions in the proximal regions of the central rod domain (exons 20-40) are generally milder than those in the distal part (exons 40-55) [Aartsma-Rus et al, 2006b;Angelini et al, 1994;Beggs et al, 1991;Gospe et al, 1989;Ishigaki et al, 1996]. In addition, it has been reported that the presence or absence of the hinge regions may influence functionality [Carsana et al, 2005;Yokota et al, 2007]. However, the beneficial effect of dystrophin restoration does not only depend on the quality of the dystrophin, but also on additional factors, because their variety in disease severity even for patients within BMD families has been reported [Nordenskjold et al, 1990].…”
Section: Overall Applicabilitymentioning
confidence: 95%
“…6,49 It was recently reported that deletions that include the third hinge region are generally associated with milder phenotypes than those that do not involve this hinge region. 10 In-frame deletions removing both the actin-binding domain and part of the central rod domain usually cause DMD. 3,17,58 This may be explained by the fact that an additional actin-binding site is present in the central rod domain.…”
Section: Relation Between Size and Location Of Mutations And Phenotypementioning
confidence: 99%